Protection Coordination Study and Analysis of Section of Integrated Nepal Power System - Yadav, Jitesh Kumar; Maharjan, Shreeshuva; Gurung, Samundra (Journal of Science and Engineering, 2025)
The increasing complexity and dynamism of modern power systems, driven by growing load demands, renewable energy integration, and network expansions has necessitated robust protection coordination strategies to ensure system reliability and operational security. This paper presents a comprehensive protection coordination study and analysis of a particular section of the Integrated Nepal Power System (INPS). The study highlights the interaction between OCRs-to-OCRs and distance relays-to-OCRs under various fault conditions. The system was modeled in DIgSILENT Power Factory, and the analysis was done accordingly. A model of a 66 kV, 65 km transmission network with two generators (17.55 MW), external grid and 30.7 MW load was simulated. Symmetrical and unsymmetrical fault scenarios were created and tested to assess primary and backup relays operations. The findings showed that the present relay settings are capable of isolating the faults under various fault conditions, ensuring the coordination time interval (CTI).